2015
DOI: 10.1121/1.4922366
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of minimum oral tract constriction area in sibilant fricatives from aerodynamic data

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The turbulence levela tt he inlet of the replica wasl ess than 3% [13]. Experiments were conducted at aflow rate of 40 L•min −1 ,which corresponds to the subject'smedium flowrate of /s/ in three effort levels, soft, medium and loud [14]. The flowrate wasvaried from 35 to 45 L•min −1 while the subject sustained /s/ at the medium level.…”
Section: Measurement With Flowmentioning
confidence: 99%
“…The turbulence levela tt he inlet of the replica wasl ess than 3% [13]. Experiments were conducted at aflow rate of 40 L•min −1 ,which corresponds to the subject'smedium flowrate of /s/ in three effort levels, soft, medium and loud [14]. The flowrate wasvaried from 35 to 45 L•min −1 while the subject sustained /s/ at the medium level.…”
Section: Measurement With Flowmentioning
confidence: 99%
“…At the inlet of the vocal tract geometry, a uniform velocity was imposed to set the constant flow rate for each vocal tract. Since we could not measure the flow rate while the subjects were sustaining /s/ in the MRI machine, we used a general flow rate of /s/ 250 cm 3 /s [9]. Meanwhile, the flow rate of subject D was increased up to 300 cm 3 /s since the sound amplitude was too small to compare with other subjects.…”
Section: Computational Grids and Boundary Conditionsmentioning
confidence: 99%
“…Because the /s/ is dependent on dental anatomy, the success of dental procedures is often assessed by determining the quality of /s/ (cf. Fujiso, Nozaki, & Van Hirtum, 2015;Mehringer, 1963;Runte et al, 2001). Fujiso et al (2015) indicated that a speech screening tool to qualitatively assess dental procedures is best when using the fricative /s/, due to its reproducibility, consistent air flow, and intraoral pressure.…”
Section: Impact Of Palatal Features On Tongue Placementmentioning
confidence: 99%
“…Fujiso, Nozaki, & Van Hirtum, 2015;Mehringer, 1963;Runte et al, 2001). Fujiso et al (2015) indicated that a speech screening tool to qualitatively assess dental procedures is best when using the fricative /s/, due to its reproducibility, consistent air flow, and intraoral pressure. In addition to the alteration of /s/ by dental treatment, natural malocclusions and dental variability can also have an effect on speech.…”
Section: Impact Of Palatal Features On Tongue Placementmentioning
confidence: 99%